Analysis of thermo-hydraulic and entropy generation characteristics for flow through ribbed-wavy channel. Issue 5 (22nd July 2021) - Mehta, Sumit Kumar; Pati, Sukumar; Ahmed, Shahid; Bhattacharyya, Prangan; Bordoloi, Jishnu Jyoti
Abstract : Purpose: The purpose of this study is to analyze the thermal, hydraulic and entropy generation characteristics for laminar flow of water through a ribbed-wavy channel with the top wall as wavy and bottom wall as flat with ribs of three different geometries, namely, triangular, rectangular and semi-circular. Design/methodology/approach: The finite element method-based numerical solver has been adopted to solve the governing transport equations. Findings: A critical value of Reynolds number (Recri ) is found beyond which, the average Nusselt number for the wavy or ribbed-wavy channel is more than that for a parallel plate channel and the value of Recri decreases with the increase in a number of ribs and for any given number of ribs, it is minimum for rectangular ribs. The performance factor (PF) sharply decreases with Reynolds number (Re) up to Re = 50 for all types of ribbed-wavy channels. For Re > 50, the change in PF with Re is gradual and decreases for all the ribbed cases and for the sinusoidal channel, it increases beyond Re = 100. The magnitude of PF strongly depends on the shape and number of ribs and Re. The relative magnitude of total entropy generation for different ribbed channels varies with Re and the number of ribs. Practical implications: The findings of the present study are useful to design the economic heat exchanging devices. Originality/value: The effects of shape and the number of ribs on the heat transfer performance and entropy generation have been investigated for the first time for the laminar flow regime. Also, the effects of shape and number of ribs on the flow and temperature fields and entropy generation have been investigated in detail.